Peningkatan Kemampuan Guru Dalam Menyusun Kelengkapan Mengajar Melalui In-House Training Pada SMK Negeri 1 Balige - Tigor Siahaan (Ability: Journal of Education and Social Analysis, 2022)
One of the efforts made is to carry out In-House Training activities in compiling teaching equipment as school action research. The purpose of this study was to improve the ability of teachers at SMK Negeri 1 Balige in preparing teaching equipment and determining the right steps to improve the teacher's ability to develop teaching equipment. With In-House Training it is hoped that all teachers will have adequate knowledge, understanding and experience, especially in preparing teaching equipment which includes the Annual Program (Prota), Semester Program (Promes) and Learning Implementation Plans (RPP) in addition to other supporting equipment such as syllabus, educational calendar , teaching schedule and list of student grades. The research was conducted at SMK Negeri 1 Balige for approximately one month starting from October 25 to December 2, 2018. Data collection was carried out through questionnaires, observation and documentation. From the questionnaire, it was found that overall the teachers of SMK Negeri 1 Balige stated that it was important to have complete teaching. Most teachers of SMK Negeri 1 Balige feel that their teaching experience is still minimal in the subjects being taught, the educational background is not very suitable for the subjects being taught and knowledge about the preparation of teaching equipment is still lacking. All teachers of SMK Negeri 1 Balige want In-House Training to prepare teaching equipment and 100% of teachers have high motivation to take part in In-House Training and have a strong desire to make teaching equipment and will use the teaching equipment to support the learning process. The research was conducted in 2 cycles. In cycle 1, it was found that 58.23% of teachers succeeded in completing the preparation of teaching equipment and in Cycle 2 there were 91.66% of teachers who succeeded in completing the preparation of teaching equipment. So there was an increase in the teacher's ability to prepare teaching equipment after the In-House Training stage 1 was carried out, namely 33.43% and each teacher showed a significant increase. In-House Training is one of the most effective ways to improve the teacher's ability to prepare teaching materials.